Evaluation of GeMa CerMat Program During The Peak of COVID-19 Pandemic in Indonesia - Soegiantoro, Didiek Hardiyanto; Soegiantoro, Holy Rhema; Soegiantoro, Gregory Hope (STIKES Yayasan RS.Dr.Soetomo, 2022)
The GeMa CerMat program from the Indonesian Ministry of Health was started in 2015 with the aim of rational drug use. The success of GeMa CerMat's goal in rational use of drugs was tested by the COVID-19 pandemic which reached its peak in June to August 2021. Public panic due to the high death rate of COVID-19 caused panic buying for drugs used in the treatment of COVID-19, including prescribed drugs. The demand for COVID-19 prescribed drugs without prescription describes the irrational use of drugs and an uncontrolled increase in demand that will lead to a shortage of drugs in distribution channels and increase the cost of purchase according to the theory of supply and demand. This study is an observational study using a cross-sectional analysis method from a number of pharmacies in each region, conducted from June to August 2021. The results showed an increase more than 2 times in demand for prescribed drugs without prescription for COVID-19 drugs, which resulted in an increase in purchasing lead times more than 3 times, as well as an increase in the cost of purchase of drugs more than 3 times and could be controlled with government selling price standard. The conclusion of this study is that the GeMa CerMat program has not succeeded in educating the public to use drugs rationally, as a result, during the peak of the COVID-19 pandemic, panic buying occurred for COVID-19 prescribed drugs which resulted in an increase in purchasing lead time and cost of purchase.